2004
DOI: 10.1523/jneurosci.2329-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Like Alterations inAplysiaAxons after Nerve Injury or Localized Depolarization

Abstract: Adaptive, long-term alterations of excitability have been reported in dendrites and presynaptic terminals but not along axons. Persistent enhancement of axonal excitability has been described in proximal nerve stumps at sites of nerve section in mammals, but this hyperexcitability is considered a pathological derangement important only as a cause of neuropathic pain. Identified neurons in Aplysia were used to test the hypothesis that either axonal injury or the focal depolarization that accompanies axonal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 73 publications
6
68
1
1
Order By: Relevance
“…Several experiments have demonstrated that dorsal root ganglion axons are translationally competent (Zheng et al, 2001;Willis et al, 2005) and that axonal translation is important for growth cone guidance and collapse (Verma et al, 2005;Wu et al, 2005) and for injury-or depolarization-induced hyperexcitability of Aplysia sensory axons (Weragoda et al, 2004). We have previously demonstrated that FMRP is transported to the peripheral axons of rat nociceptors (Price et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several experiments have demonstrated that dorsal root ganglion axons are translationally competent (Zheng et al, 2001;Willis et al, 2005) and that axonal translation is important for growth cone guidance and collapse (Verma et al, 2005;Wu et al, 2005) and for injury-or depolarization-induced hyperexcitability of Aplysia sensory axons (Weragoda et al, 2004). We have previously demonstrated that FMRP is transported to the peripheral axons of rat nociceptors (Price et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Axonally synthesized proteins appear to play an important role in nerve regeneration and repair after injury (Willis and Twiss, 2006), and local, axonal translation is required for injuryinduced hyperexcitability of Aplysia axons (Weragoda et al, 2004). We predicted that, if FMRP regulates the translation of proteins that mediate nerve injury-induced hyperexcitability in axons, the development of neuropathic allodynia would be delayed (because these proteins would have to be transported from the soma, rather than synthesized locally) or even absent in Fmr1 KO mice.…”
Section: Delayed Development Of Nerve Injury-induced Allodynia In Fmrmentioning
confidence: 99%
“…Beyond morphological rearrangements, the axon is also able to express many forms of functional plasticity (520,557). In fact, several lines of evidence suggest that ion channel activity is highly regulated by synaptic or neuronal activity (reviews in Refs.…”
Section: B Functional Plasticitymentioning
confidence: 99%
“…These include axonal regeneration and sprouting of neurites near a site of peripheral injury and within central ganglia [Billy and Walters, 1989;Steffensen et al, 1995]. Peripheral injury also causes a decrease in mechanosensory threshold in the damaged region [Billy and Walters, 1989;Dulin et al, 1995], a decrease in electrical threshold of the nociceptor axon near a site of injury or of intense, transient depolarization [Weragoda et al, 2004], and an increase in excitability of the nociceptor soma . Soma hyperexcitability promotes afterdischarge ( fig.…”
Section: Long-term Nociceptive Sensitization In Molluscs: Functional mentioning
confidence: 99%